2016
DOI: 10.1155/2016/3701468
|View full text |Cite
|
Sign up to set email alerts
|

Trainers’ Attitudes towards Cardiopulmonary Resuscitation, Current Care Guidelines, and Training

Abstract: Objectives. Studies have shown that healthcare personnel hesitate to perform defibrillation due to individual or organisational attitudes. We aimed to assess trainers' attitudes towards cardiopulmonary resuscitation and defibrillation (CPR-D), Current Care Guidelines, and associated training. Methods. A questionnaire was distributed to CPR trainers attending seminars in Finland (N = 185) focusing on the updated national Current Care Guidelines 2011. The questions were answered using Likert scale (1 = totally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The greater the nurses' resuscitation self-efficacy in responding to emergency situation, the greater would be the expectation for consistently strong determinants and predictors of the level of accomplishment towards successful patient survival. 4 The findings of this study indicated that the nurses working in the private hospital have a relatively high sense of self-efficacy in CPR resuscitation. Congruently, Mäkinen et al (2016; 2014) [4][5] stated that in Greece and Sweden, nurses' self-efficacy is associated with satisfactory performance of CPR skills, even though an effective resuscitation requires a combination of competencies in knowledge, technical and non-technical skills.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The greater the nurses' resuscitation self-efficacy in responding to emergency situation, the greater would be the expectation for consistently strong determinants and predictors of the level of accomplishment towards successful patient survival. 4 The findings of this study indicated that the nurses working in the private hospital have a relatively high sense of self-efficacy in CPR resuscitation. Congruently, Mäkinen et al (2016; 2014) [4][5] stated that in Greece and Sweden, nurses' self-efficacy is associated with satisfactory performance of CPR skills, even though an effective resuscitation requires a combination of competencies in knowledge, technical and non-technical skills.…”
Section: Discussionmentioning
confidence: 69%
“…4 The findings of this study indicated that the nurses working in the private hospital have a relatively high sense of self-efficacy in CPR resuscitation. Congruently, Mäkinen et al (2016; 2014) [4][5] stated that in Greece and Sweden, nurses' self-efficacy is associated with satisfactory performance of CPR skills, even though an effective resuscitation requires a combination of competencies in knowledge, technical and non-technical skills. However, several studies reported that there were gaps between recommendations from recommended guidelines and reality in CPR training, and the gap between training frequency and real resuscitation experience.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation